PENGARUH PROFITABILITAS, SOLVABILITAS, DAN SIZE PERUSAHAAN TERHADAP TIMELINESS LAPORAN KEUANGAN PADA PERUSAHAAN YANG TERDAFTAR DI BEI TAHUN 2016 – 2021 - Reza Al Muttaqin Herson; Taufiq Hidayat (Journal of Accounting, Management and Islamic Economics, 2023)
This study aims to determine the effect of profitability, solvency and company size on the timeliness of financial statements listed on the Indonesia Stock Exchange. The research sample is that companies are late in submitting their financial statements in 2021 and already have financial reports from 2016-2021. Of the number of late companies listed on the IDX as many as 8 companies. 8 companies used as research samples. The dependent variable used is the timeliness of financial reports. The independent variables used are profitability as proxied by Return on Assets (ROA), Solvency by Return on Equity (ROE), and company size as proxied by Ln (total assets). The results of this study indicate that solvency has a negative effect on the timeliness of financial reports. While profitability has no effect on the timeliness of financial reports. And the size of the company has a positive effect on the timeliness of financial reports.